Influenza virosomes as a vaccine adjuvant and carrier system. (April 2011) - Moser, Christian; Amacker, Mario; Zurbriggen, Rinaldo
Influenza virosomes have been used for more than 10 years in commercial vaccines. The technology has been further developed as a carrier and adjuvant system for subunit vaccines, in particular for synthetic peptides. The extensive amount of preclinical and clinical data supports the notion that influenza virosomes represent a platform technology that ensures robust and long-lasting immune responses against subunit antigens with an excellent safety profile. Structurally and functionally, virosomes are enveloped virus-like particles, although they are assembled in vitro . This unique feature ensures a tight control of their composition and at the same time provides the flexibility to adapt the particle to various types of antigens. The mode of action of virosomes is complex and includes carrier as well as immune-stimulatory functions.